Effects of active vitamin D analogues on muscle strength and falls in elderly people: an updated meta-analysis - Xiong, An; Li, Haibo; Lin, Miaoying; Xu, Feng; Xia, Xuedi; Dai, Dexing; Sun, Ruoman; Ling, Yali; Qiu, Lei; Wang, Rui; Ding, Ya; Xie, Zhongjian (Frontiers in Endocrinology, 2024)
Background: Elderly people are at high risk of falls due to decreased muscle strength. So far, there is currently no officially approved medication for treating muscle strength loss. The active vitamin D analogues are promising but inconsistent results have been reported in previous studies. The present study was to meta-analyze the effect of active vitamin D analogues on muscle strength and falls in elderly people.The protocol was registered with PROSPERO (record number: CRD42021266978). We searched two databases including PubMed and Cochrane Library up until August 2023. Risk ratio (RR) and standardized mean difference (SMD) with 95% confidence intervals (95% CI) were used to assess the effects of active vitamin D analogues on muscle strength or falls.Results: Regarding the effects of calcitriol (n= 1), alfacalcidol (n= 1) and eldecalcitol (n= 1) on falls, all included randomized controlled trials (RCT) recruited 771 participants. Regarding the effects of the effects of calcitriol (n= 4), alfacalcidol (n= 3) and eldecalcitol (n= 3) on muscle strength, all included RCTs recruited 2431 participants. The results showed that in the pooled analysis of three active vitamin D analogues, active vitamin D analogues reduced the risk of fall by 19%. Due to a lack of sufficient data, separate subgroup analyses were conducted on the effect of each active vitamin D analogue on falls. In the pooled and separate analysis of active vitamin D analogues, no significant effects were found on global muscle, hand grip, and back extensor strength. However, a significant enhancement of quadriceps strength was observed in the pooled analysis and separate analysis of alfacalcidol and eldecalcitol. The separate subgroup analysis on the impact of calcitriol on the quadriceps strength was not performed due to the lack to sufficient data. The results of pooled and separate subgroup analysis of active vitamin D analogues with or without calcium supplementation showed that calcium supplementation did not affect the effect of vitamin D on muscle strength.The use of active vitamin D analogues does not improve global muscle, hand grip, and back extensor strength but improves quadriceps strength and reduces risk of falls in elderly population.